One two three [large type] - Frankel, Laurie (Thorndike press large print basic, 2021)
"Everyone knows everyone in the tiny town of Bourne, but the Mitchell triplets are especially beloved. Mirabel is the smartest person anyone knows, and no one doubts it just because she can't speak. Monday is the town's purveyor of books now that the library's closed--tell her the book you think you want, and she'll pull the one you actually do from the microwave or her sock drawer. Mab's job is hardest of all: get good grades, get into college, get out of Bourne. For a few weeks seventeen years ago, Bourne was national news when its water turned green. The girls have come of age watching their mother's endless fight for justice. But just when it seems life might go on the same forever, the first moving truck anyone's seen in years pulls up and unloads new residents and old secrets. Soon, the Mitchell sisters are taking on a system stacked against them and uncovering mysteries buried longer than they've been alive. Because it's hard to let go of the past when the past won't let go of you. Three unforgettable narrators join together here to tell a spellbinding story with wit, wonder, and deep affection. As she did in This Is How It Always Is, Laurie Frankel has written a laugh-out-loud-on-one-page-grab-a-tissue-the-next novel, as only she can, about how expanding our notions of normal makes the world a better place for everyone and how when days are darkest, it's our daughters who will save us all"--